Hubungan Stres Akademik dan Pola Tidur dengan Ketidakteraturan Siklus Menstruasi pada Mahasiswi - Fika Daulian; Faridha Almira (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
Menstrual cycle irregularity is an important indicator of hormonal imbalance that may affect women’s reproductive health. Female university students are particularly vulnerable to menstrual irregularities due to academic pressure and unhealthy lifestyle patterns, including inadequate sleep. This study aimed to analyze the association between academic stress and sleep patterns with menstrual cycle irregularity among female university students. This study employed a quantitative approach with a cross-sectional design and was conducted among undergraduate female students of the Faculty of Public Health, Universitas Cenderawasih. A total of 196 respondents were selected using purposive sampling. Data were collected using structured questionnaires to assess academic stress levels, sleep patterns, and menstrual cycle regularity. Bivariate analysis was performed using the Chi-square test with a significance level of 0.05. The results showed that academic stress was significantly associated with menstrual cycle irregularity (p = 0.043). Sleep patterns were also significantly associated with menstrual cycle irregularity (p = 0.016). In conclusion, academic stress and inadequate sleep patterns are significantly associated with an increased occurrence of menstrual cycle irregularity among female university students. These findings highlight the importance of stress management and healthy sleep practices as part of health promotion efforts in university settings.